ANALISIS SIKAP KONSUMEN DALAM MENGONSUMSI MADU SIALANG PRODUKSI MR. HONEY DI KOTA PEKANBARU - Rangga Rahadi Putra; Rosnita ' (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
Small medium enterprise (SME) Mr. Honey is an SME that is run by a student of Agribusiness Department Faculty of Agriculture University of Riau in Pekanbaru City. The product is still very simple, nevertheless demand on Mr. Honey’s product is still continuing. This may happen due to some attributes on Mr. Honey’s product that become the consideration for consumers, so the consumers keep purchasing the product from Mr. Honey. The research aims to analyze the consumers’ characteristic, consumers’ attitude, and to figure out the performance of SME Mr. Honey. The results showed that the characteristic of Mr. Honey’s consumers were single and productive young female, acquiring higher education, as well as having proper and well paid job. The attitude of consumers was positve, shown by the score 20.18 which meant it was good.The performance on attributes that must be maintained by SME Mr. Honey were hygiene attribute, originalitiy, ease in obtaining, and fair price. Meanwhile, the attributes that were include as main priority to be improved were the attachment of nutrition facts on the product, brand, Label of National Agency of Drug and Food Control, and also packaging of Mr. Honey’s products. Keywords: Attributes, Consumers’ Characteristics, Consumers’ Attitude, Performance